Association of HLA-G Low Expressor Genotype with Severe Acute Graft-Versus-Host Disease after Sibling Bone Marrow Transplantation - Boukouaci, Wahid; Busson, Marc; Fortier, Catherine; Amokrane, Kahina; Peffault de Latour, Régis; Robin, Marie; Krishnamoorthy, Rajagopal; Toubert, Antoine; Charron, Dominique; Socié, Gérard; Tamouza, Ryad (Frontiers in Immunology, 2011)
Background HLA-G molecules play a prominent role in immune tolerance. Structurally similar to their classical HLA homologues, they are distinct by having high rate of polymorphism in the non-coding regions including a functionally relevant 14 base pair (bp) insertion/deletion (Ins/Del) allele in the 3’ untranslated region (3’UTR), rarely examined in a hematopoietic stem cell transplantation (HSCT) setting. Here, we analyzed the potential impact of HLA-G Ins/Del dimorphism on the incidence of acute graft versus host disease (aGvHD), transplant related mortality (TRM), overall survival (OS) and incidence of relapse after HSCT using bone marrow as stem cell source from HLA matched donors. Methods One hundred and fifty seven sibling pairs, who had undergone HSCT, were studied for the distribution of the HLA-G 14bp Ins/Del polymorphism using a polymerase chain-reaction (PCR)-based technique. Potential genetic association with the incidence of aGvHD, TRM and OS was analyzed by uni- and multivariate analyses. Results Univariate analysis showed that the homozygous state for the 14 bp Ins allele is a risk factor for severe aGvHD (grade III and IV) (P = 0.008), confirmed subsequently by multivariate analysis (hazard ratio  HR  = 3.5; 95% confidence interval 95%CI = 1.3-9.5; P = 0.012). We did not find any association between HLA-G polymorphism and the other studied complications. Conclusions Our data suggest that the HLA-G low expressor 14bp Ins allele constitutes a risk factor for the incidence of severe aGvHD in patients who received bone marrow as stem cell source.